2017
DOI: 10.5942/jawwa.2017.109.0096
|View full text |Cite
|
Sign up to set email alerts
|

State Barriers to Approval of Drinking Water Technologies for Small Systems

Abstract: One perceived barrier to the implementation of new technologies in small drinking water systems is obtaining state regulatory agency approval. To investigate barriers as well as acceptance program status, experiences with new technologies, data needs for technology approval, and interest in a shared approach to acceptance of new technologies, a survey was sent to state regulatory agencies. The survey confirmed that new technologies for small systems are rarely considered by agencies. Key barriers encountered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…RBF represented a potentially effective option to reduce the production of THMs in small systems. The occurrence of THMs in small systems represents a challenge for local water utilities [2,15,49]. For example, Hua et al [2], investigating three small drinking water systems in rural Missouri using groundwater, surface water, and reservoir water as source water reported high levels of THMs (>80 µg L −1 ) in finished water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RBF represented a potentially effective option to reduce the production of THMs in small systems. The occurrence of THMs in small systems represents a challenge for local water utilities [2,15,49]. For example, Hua et al [2], investigating three small drinking water systems in rural Missouri using groundwater, surface water, and reservoir water as source water reported high levels of THMs (>80 µg L −1 ) in finished water.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hua et al, investigating three small drinking water systems in rural communities in Missouri, observed consistently higher THMs in finished water than the MCL (80 µg L −1 ) [2]. Nationally, it has been identified that small systems using surface waters experience three times the rate of Stage 1 DBP violations than systems that serve populations above 10,000 [15]. Therefore, there is a need to provide cost-effective solutions to improve the source of water by reducing its variations and lowering its level of organic carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…i Compartir información relacionada con la innovación Concepto. El escaso acceso a la información que los prestadores de servicios de AyS tienen por sus propios medios, así como a través de sus proveedores, o el riesgo de que estos últimos resulten poco serios pueden influir en su aversión al riesgo y aumentar la barrera para la innovación sectorial, principalmente en los prestadores de menor tamaño (Ringenberg, 2017). Por ello, es fundamental compartir información, por ejemplo, a través de una red de intercambio que permita proporcionar datos de estudios realizados en otras zonas geográficas (provincias, estados, etc.…”
Section: M P L E M E N T a C I ó Nunclassified